The importance of checking the emotions of parents with children with autism spectrum disorder (ASD) - Reyes Cortijo, Gladys Lily Amparo (2019)
The following article hopes to briefly mention the emotions that parents of children with autism usually present. Some of the emotional states of these parents, as the days, months and years pass, influence the emotional progress of their children, therefore it is important to provide emotional support in the short and long term. Before starting the writing of this article, I conducted a survey of a single question among people around me about autism. All of them randomly chosen with only two unique points in common, neither of them has children, nor studies in teaching, psychology or similar. Before the question: how would you take the new that your child is autistic?, these were some of the answers I received: “we do not have that problem in my family”, “my husband and I are young”, “I would not be satisfied with a single result”, “for that we planned”, among others. Personally, all these responses are natural of the human being: denial, resilience, shame, etc., that is why I consider acceptable all their answers since they do not know the concepts, theories or studies on ASD. In this article it will mention some important concepts that will give us an idea about ASD and the emotions that affect the parents of the children who have it.